The Influence of Green Culture on Sustainability Development Goals (SDGs) With GCG Variables as A Moderation - Usmar, Usmar; Prihanto, Hendi; Lanori, Tamrin; Selfiani, Selfiani (Lafadz Jaya Publisher, 2024)
Green culture, an organizational approach centered on environmental consciousness and practices, plays an increasingly significant role in promoting Sustainable Development Goals (SDGs). This study investigates the influence of green culture on the progress of SDGs, focusing on the integration of Good Corporate Governance (GCG) as a moderating variable. Through this exploration, we aim to understand how GCG can either enhance or hinder the effectiveness of green culture initiatives toward achieving specific SDG targets. This research uses a quantitative approach, analyzing data from organizations implementing green culture practices alongside structured GCG frameworks. Results indicate that companies that prioritize green culture see measurable improvements in meeting SDG objectives, especially in areas like resource management, waste reduction, and energy efficiency. The moderation effect of GCG shows that governance policies significantly influence the success of green initiatives, either amplifying their benefits or presenting challenges in aligning with sustainability goals. Key findings highlight that effective GCG not only supports environmental practices but also enhances organizational transparency and stakeholder trust. This study underscores the need for organizations to adopt integrated approaches where green culture and GCG work in synergy to maximize the positive impacts on SDG achievements. Such a framework can serve as a model for sustainable development, providing a pathway for businesses to balance profitability with global environmental and social responsibilities.